2006
DOI: 10.1111/j.1365-2648.2006.03751.x
|View full text |Cite
|
Sign up to set email alerts
|

Promoting evidence‐based practice: the roles and activities of professional nurses’ associations

Abstract: Professional nurses' association roles in the promotion of evidence-based practice need to be viewed in relation to the tasks to be accomplished, especially those of selecting and distributing evidence. Although many organizations expressed motivation, professional nurses' associations have a long way to go in the promotion of evidence-based practice among their members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Organizations were more likely to be active and succeed if advocacy functions were written into organizational policies, strategic plans, and goals [26,56,61]. While few references were made, the nursing literature confirmed that organization policy might serve to support and enhance policy advocacy initiatives [81].…”
Section: Factors Influencing Priority Setting and Policy Advocacymentioning
confidence: 99%
See 4 more Smart Citations
“…Organizations were more likely to be active and succeed if advocacy functions were written into organizational policies, strategic plans, and goals [26,56,61]. While few references were made, the nursing literature confirmed that organization policy might serve to support and enhance policy advocacy initiatives [81].…”
Section: Factors Influencing Priority Setting and Policy Advocacymentioning
confidence: 99%
“…Within these membership configurations, motives for joining organizations, and the backgrounds, perspectives, interests, skills, and expertise of members were diverse. Organizations with more homogeneous membership facilitated an organization's ability to speak with one voice [26,64,81]. However, diversity enhanced access to highlevel policy-makers and added legitimacy to their voice [26].…”
Section: Factors Influencing Priority Setting and Policy Advocacymentioning
confidence: 99%
See 3 more Smart Citations